ANALISIS PENGARUH DESENTRALISASI FISKAL DAN PEMBANGUNAN INFRASTRUKTUR TERHADAP KETIMPANGAN PENDAPATAN 6 PROVINSI DI PULAU JAWA TAHUN 2013-2022 - Muhammad Iqbal; Nenik Woyanti (Universitas Muhammadiyah Semarang, 2025)
The trend of fiscal decentralization and infrastructure development such as roads, sanitation, and electricity in the 6 provinces on the island of Java, which tends to increase every year, should be able to reduce inequality. However, on the contrary, this condition of inequality has not significantly improved. The average Gini index in 6 provinces on the island of Java from 2013-2022 was 0.395, while the national average for the same period was 0.391. This indicates a serious problem regarding income inequality in Java. This study aims to analyze the influence of fiscal decentralization and infrastructure development on income inequality in 6 provinces on the island of JavaThe analysis method used in this study is panel data regression using the Fixed Effect Model (FEM). This study uses 60 secondary data points. The data used in this study were sourced from the Central Bureau of Statistics and the Ministry of Finance.Based on the research findings, it was found that the fiscal decentralization variable had a significant positive effect on income inequality. The sanitation variable had a significant negative effect on inequality. Furthermore, the road and electricity variables did not have a significant effect on income inequality.